[Aerial View of Cal Poly] - John H. Klopp::::::photographer::: (1949)
Inscription on back: "Main campus: General Views - looking northeast from Southern Pacific railroad to Santa Lucia Mountains", Caption on identical photo: "Brizziolari Creek Watershed in part, top center of photo estimated 1000 acres. Drumm Lake (Reservoir) center left. Diversion ditch to start above junction of field area and creek.", Caption on identical photo: "Aerial view showing Cal Poly Campus and a portion of the 2000 acres of farm and grazing land used in agricultural instruction. On the reverse side is a similar aerial view with building groups identified. (see ua-pho_00001253" Dexter is under construction in the photo.